Anti-proliferative effects of cu(phen)(c-dimethylglycine)NO3 on HT-29 and A2780 cancer cell lines: a potential chemotherapeutic approach - Zainudin, Nurfarahdilla; Theng, Ng Chin; Yen, Fong Lai; Keong, Yong Yoke; Hakim, Muhammad Nazrul; Ahmad, Zuraini (Innovare Academics Sciences Pvt. Ltd, 2025)
Objectives: This study aimed to evaluate the in vitro antiproliferative properties of Cu(Phen)(C-dimethylglycine)NO3 on human cancer cell lines. Specifically, the study investigated its effects on the proliferation of colorectal carcinoma (HT-29) and ovarian carcinoma (A2780) cells, determined the IC50 values, measured caspase-9 activity, and assessed the degree of DNA fragmentation. Methods: The antiproliferative and apoptotic effects of standardized Cu(phen)(C-dimethylglycine)NO3 were evaluated at varying concentrations (1, 2, 5, 10, 15, and 20 µM) over 24, 48, and 72 h. Cell viability was assessed using the MTT assay, whereas caspase-9 activity was measured using fluorometric assay kits and a fluorophotometer. DNA fragmentation was analyzed using the Cell Death Detection ELISA Plus kit. Results: The results demonstrated a time- and concentration-dependent reduction in cell viability for both cell lines. Notably, A2780 cells exhibited a lower IC50 (1.76 ± 0.406 µM at 72 h) compared to HT-29 cells (7.03 ± 0.635 µM), indicating greater sensitivity. However, the compound did not significantly alter caspase-9 expression nor induce DNA fragmentation when compared to the control. Conclusion: Cu(phen)(C-dimethylglycine)NO3 exerts a significant anti-proliferative effect without triggering apoptosis, suggesting a non-apoptotic mechanism of cytotoxicity that warrants further investigation.